Dampak Nikah Shigar terhadap Generasi Muda - Farhan Abbas; Riyadhul Jinan; Raia Humaini; Aditia Lahakam; Hikmatullah Hikmatullah (TADHKIRAH: Jurnal Terapan Hukum Islam dan Kajian Filsafat Syariah, 2026)
The impact of sighar marriage on the younger generation from the perspective of Islamic law, social, and psychological. The main problem raised is the practice of marriage without dowry which places women as objects of exchange, thus ignoring their rights and causing the invalidity of the contract according to a number of scholars. The purpose of this study is to analyze the social, legal, and religious consequences of sighar marriage and its implications on the formation of children's identity and family resilience. The research method uses a literature study with a normative-comparative approach, referring to classical fiqh literature, hadith, and contemporary academic studies that compare the views of the Shafi'i, Maliki, Hanbali, and Hanafi schools. The results of the study show that nikah syighar has an impact on the neglect of women's rights, the normalization of objectification, household instability, the crisis of children's identity, and the weakening of family institutions. In addition, this practice is contrary to maqasid al-shari'ah, thus undermining the sacred value of marriage as worship and a means of moral development. These findings underscore the need for Islamic family law regulation and education to protect the younger generation from the practice of illegal and harmful marriage.